Gender Discrimination or Respect? - Soheil Dastmalchian Khorasani (Humanities Today: Proceedings, 2023)
In recent years, sociologists pay special attention to the challenging issue of sexual discrimination which has been converted to a hot topic nowadays. The main issue is why women are inhibited to attend in a special socio cultural events despite of presence law, rule and regulation in that area. So, in order to find out the answer of this question, the authors decided to conduct an analytic short communication using a search in the literature. As the main problem was emerged in Iran, besides reviewing International documents and conventions allocated to women, national – Iranian- literature such as academic papers, reports, newspapers and magazines were also searched. Comparing the written documents to real situations showed inconsistency; because although there was no limitation for participating women in such activities, the execution of laws has been failed. The barriers seem to be categorized in Macro and Micro levels which could be resolved by clarifying, defining and planning specific strategies in their related area. Obviously, in depth exploration of the major concept need qualitative studies.